Availability of informal social support and the impact on health services utilization among women in community corrections who engage in substance use and risky sexual behavior: New York City, 2009-2012 - Karli R. Hochstatter; Melissa N. Slavin; Louisa Gilbert; Dawn Goddard-Eckrich; Nabila El-Bassel (BMC, 2022)
Abstract Background Women under community supervision in the U.S. experience high rates of substance use and HIV/STDs and face multiple barriers to healthcare services. Informal social support, provided by family, friends, and other peers, is important for reducing drug and sexual risk behaviors and improving utilization of healthcare services. The availability of informal social support and the impact on receipt of healthcare services among the growing and highly vulnerable population of sexually-active and drug- and justice-involved women has not been documented. Among this population, this study aims to: 1) describe characteristics of informal social support, including the prevalence of different types, size of networks, and frequency of receiving support; and 2) longitudinally examine the impact of informal social support on receipt of healthcare services, including drug or alcohol counseling/treatment, HIV or STD counseling/education, birth control counseling/education, reproductive healthcare, and individual counseling over a 12-month period. Results The sample included 306 women in community supervision programs in New York, New York, USA, with a recent history of substance use and risky sexual behavior. At baseline, 96.1% of women reported having at least one friend or family member with whom they could discuss personal or emotional problems, 92.5% had support for tangible aid or service, 83.0% had support for sexual risk reduction, and 80.0% had support for substance use risk reduction. Women with support for substance use risk reduction were more likely than women without this type of support to receive all health services analyzed in this study. Having support for sexual risk reduction was also positively associated will receipt of all services, except reproductive healthcare. Having support for personal or emotional problems was only associated with receiving drug or alcohol counseling or treatment, while having support for tangible aid or service did not impact receipt of any health services. Conclusions Engagement of sexually-active and drug- and justice-involved women in health services should address the availability and strengthening of informal social support, particularly ensuring individuals' informal networks allow for discussions on the harms of risky sexual and drug use behaviors. Trial registration ClinicalTrials.gov NCT01784809 . Registered 6 February 2013 - Retrospectively registered.